Strategic Leadership in Engineering Management: Navigating the Complexities of Innovative Projects - Naser Muftah Alferjani (African Journal of Advanced Pure and Applied Sciences, 2023)
Modern engineering projects are complex due to globalization, sustainability concerns, rapid technological advances, and regulatory requirements. Strategic leadership is essential to successfully address these challenges. This article examines various aspects of strategic leadership in engineering management by looking at key theories, decision-making methods, dynamics within teams, and suggested practices. We explain how successful strategic leadership improves project outcomes, stimulates creativity, and promotes organizational success through studies of literature and case studies. The findings highlight the importance of communication from ongoing education, flexible project management, and expertise in overcoming contemporary project obstacles.